The new political subject: autonomy and heteronymy with special reference to the citizen peace movement - Sandoval, Luis (Universidad Pedagógica y Tecnológica de Colombia, 2003)
The peace in Colombia deeply is bound to the transformation of the policy. Of political actors with precarious legitimacy and representation the peace cannot be expected. The inacabadas society and the Nation which they constitute the Colombia of today, which is reflected in acute and chronic confrontations of diverse nature, requires to turn independent political project the accumulated ones of democratizadoras causes that have populated the life with the country in last the five decades. That national, innovating country, has to find the way and the form to control to I expire political country. The independent political project consists of constructing a incluyente society that plays a role of structural mediation between the establishment and the political rebellion from proposing an exit to the deep social deficit. Of there the articulador central paper of a great movement of democratic transformation that corresponds to him to play the social movement of peace. In the middle of the drama and the tragedy the new political subject arises, in where the academy is protagonist.